An Analysis of Axial Magnetic Coupling Force and Torque Dependencies on Its Structure Parameters Using a 3D FEM - Robertas Lukočius; Andrius Vilkauskas; Povilas Marčiulionis; Valdas Grigaliūnas; Žilvinas Nakutis; Ramūnas Deltuva (Applied Sciences, 2022)
This paper presents research on the mechanical characteristics of a synchronous axial magnetic coupling. The influence of the coupling structure on torque and axial force was analyzed. The considered parameters of the structure include the half-clutch diversity, the air-gap length between adjacent magnets, the magnetic characteristics of the backings’ material, and the shape of the backings. It was discovered that the ferromagnetic backings that partially shroud magnets of the coupling cause a significant decrease of the maximum torque. The maximum torque and the maximum axial force decrease in nonlinear manner in response to the increasing magnets’ height diversity, and the sensitivity of the parameters is larger in the upper range of the diversity. It was also disclosed that the air-gap length between the adjacent magnets has a minor influence on torque if the total volume of magnets is constant. A quantitative comparison of the maximum torque and maximum axial force for the couplings with both ferromagnetic backings, one ferromagnetic backing and with non-ferromagnetic backings is provided. The results were obtained using a 3D FEM numerical simulation. Physical experiments were performed for the numerical model verification.